Development of a digital canva-based interactive e-module by using geogebra for high school statistics material - Nidya Rizkiani; Jumroh Jumroh; Lusiana Lusiana; Stevan Vucelja; Ibon Mugica Uriszar (JINoP (Jurnal Inovasi Pembelajaran), 2024)
The Merdeka Curriculum has an up-to-date flow of learning objectives in statistics material, especially data presentation. However, most students still need help presenting data because teaching materials at school only use printed books. This research aims to produce digital-based interactive e-module development products using the application Canva-assisted Geogebra in high school statistics material that meets the criteria of being valid, practical, and having potential effects. The research method used is R & D (research and development). The development model in this research refers to the ADDIE model, which consists of stages of analysis (analysis), level design (plan), level of development (development), level implementation (implementation), and stage evaluation (evaluation). The trial was conducted on 41 class XI students at SMA Negeri 11 Palembang. Data was obtained from validation questionnaires for validity, student response questionnaires for practicality, and student learning outcomes tests to see potential effects. The results of the research obtained that Canvas digital interactive e-module product assisted by Geogebra on high school statistics material was categorized as very valid (88.04%), efficient (90.26%), and had an effect which was categorized as good (86.81%). The results of this development should be used as teaching materials and learning media in presenting statistical material, especially the scatter diagram sub-material data. It is hoped that teachers can apply the results of this research in presenting statistical material in class, especially the scatter diagram sub-material.